Alginate lyase of a novel algae fermentation strain - Zhang, Wen (Array, 2019)
A novel algae fermentation strain was obtained in our previous work. This strain can produce alginate lyase and alcohol dehydrogenase used for the ethanol fermentation from algae. This research investigated the fermentation, separation and purification of alginate lyase, and the molecular weight of alginate lyase was determined. The optimum conditions for enzyme fermentation were as follows: fermentation medium with 20 g L–1 alginate, initial pH 6.0, and temperature 35 °C. The flasks were cultured in a shaking incubator at 120 rpm for 96 h. The enzyme was purified using the method of salting out, dialysis, and gel chromatography. After purification, the SDS-PAGE method was used to determine the molecular weight of the protein. The molecular weight of alginate lyase was 30–35 KDa. This research contributes to algae biodegradation and fuels production from algae.